Perkembangan Infrastruktur Solok Selatan Pasca Pemekaran 2005-2020 - Tiara Pujasutra; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2021)
This research aims to find out the development of infrastructure in Solok Selatan Regency after experiencing creation of new regency from 2005 to 2020. This reseacrh is important to know how the development of Solok Selatan is seen in terms of infrastructure development whether there is progress or nothing at all. The method used in this research is a historical method that include four stages, namely heuristic, source critism, interpretation, and historiography. The result showed that from 2005 to 2020 there were several infrastructure developments, one of which was in the field of road infrastructure, bridges, irrigation, education infrastructure, health infrastructure, and others. Infrastructure as one of the main supporting factors in economic growth directly or indirectly affect the lives of the people of Solok Selatan Regency, especially in the sosial and economic fields both affecting positive or negative changes. Despite these impact, the development of this infrastructure is needed in order to go to more advanced and developed Solok Selatan Regency.